Risk factors associated with the failure of secondary alveolar bone grafting with autologous iliac crest bone in patients with alveolar cleft defects: a systematic review - Wu, Jiangyi; Zhuang, Jun; Ma, Yuan; Yin, Lin; Wang, Yongqian (Frontiers in Oral Health, 2025)
PurposeThis study aimed to perform a systematic review of the risk factors associated with secondary alveolar bone grafting (SABG) failure in patients with cleft alveolus.MethodsA comprehensive search was conducted across PubMed, Scopus, Embase, and Web of Science databases from their inception to 24 February 2025, to identify relevant studies. The search keywords included “alveolar cleft” combined with either “survival” or “failure.” Studies that investigated risk factors for the failure of SABG using autologous iliac crest bone were included in this review. Relevant data, including odds ratios, hazard ratios, or comparisons of variables between patients with and without SABG failure, were recorded and analyzed.ResultsA total of nine studies, encompassing 1,855 grafts, were included. The most commonly used definition of SABG failure was Bergland grade 3 or 4. Reported failure rates varied significantly across studies, ranging from 1.0% to 45.1%. The primary risk factors for SABG failure included increased age at SABG (reported in four studies), poor oral hygiene (two studies), and the presence of an erupted lateral or canine tooth (three studies). Additionally, non-Caucasian ethnicity, international adoptee, large cleft size, a history of cleft lip/palate revision or oronasal fistula, nasoalveolar molding, and premaxillary osteotomy were also associated with a higher risk of SABG failure. No significant association was found between SABG failure and sex, alveolar cleft type (bilateral or unilateral), preoperative expansion, or preoperative orthodontics.ConclusionsThe definition of SABG failure varied across studies, with Bergland grade 3 or 4 being the most commonly used criteria. The primary risk factors for SABG failure included increased age, poor oral hygiene, and the presence of an erupted lateral or canine tooth. Surgeons should be aware of these risk factors to optimize surgical strategies and guide patients effectively.